Konstruksi Kesetaraan Gender (Keluarga Pasangan Karier di Kabupaten Wonosobo) - Nur Afida, Herlina; Zhafiri Muhammad, Hasman; Nasution, Khoiruddin (Qanun: Jurnal Hukum Keluarga Islam, 2023)
Harmony is something that is always desired by families of career couples, but reality shows that gender inequality often occurs in families where the husband and wife both work outside the home. This article aims to elucidate the condition of dual-career couples' families in the village of Tosari Rejo and how they establish gender equality within the family. The research type in this article is field research. Data collection in this study was conducted through observation, interviews, and documentation. The research findings indicate that the construction of gender equality in dual-career couples' families in Tosari Rejo Village can be achieved through various combinations of roles between husbands and wives. Out of the six families who served as informants in this study, they have good gender partners in decision-making, financial management, and child-rearing. However, in terms of domestic work, not all husbands are aware of the need to contribute to household chores, so wives are not burdened with a dual role.